Philantropía en los nombres divinos de Pseudo Dionisio - Cavallero, Pablo A. (Byzantion Nea Hellás, 2015)
The present work takes the concept of philanthropy from the pagan texts of the greek antiquity to the treatise De divinis nominibus of Dionysius the Areopagite. We conclude:1. Dionysius takes the originating conception, that philanthropía is a divine trait, it is the love of gods to the humanity; nevertheless, as a christian author, he applies this affection to the Christ, but emphasizing his superlative degree and the irrefutable proof of this love in his humanization.2. On other hand, Dionysius also takes the second line which already the Antiquity observed in the concept of philanthropía: as reflection of the divine exemplar action, the man also has to love his fellow creatures and to show this in courtesy, mercy, clemency. But this second line assumes in the christian Dionysius a bigger degree: the éros or enamouring of the man to his God, which makes him able to the martyrdom as reflection of the sacrifice in the Cross, it brings to that this love to God to be the source of the love of man to his fellows; the christian will love the others and will be peaceful with them -inclusively in spite of their indignity or enmity-, not because of themselves but because of the love to God, in order that men are creatures of God.3. Dionysius takes up the patristic conception which considers the Incarnation and the Person of the Christ as a true love to the humanity‟, and he adheres to the authors who do not disdain the use of this term, millenary already in that time.4. The use of the term philanthropía confirms the christian position of this author, who is influenced by the neoplatonism, at the same time that it attaches with the mystic key which Dionysius sees in the relation between God and men: the man never will be able to understand God, but the reading of the Scriptures, the prayer, the liturgy, the imitation of the Christ bring him to the way of access to God, which is the loving and mystic union.